The benefits of codevelopment for talent management: A case study in the banking sector - Gonzalo, Pedro; Bonneton, Domitille (Management international / International Management / Gestiòn Internacional, 2024)
Talent management is crucial for companies in the current business context, and yet, one of its components, talent development, remains largely under-researched. In this paper, we explore the relevance of an experiential learning method, namely codevelopment, as a novel talent development practice. Codevelopment aims to improve one's own professional practice by helping peers to enhance their own practice in turn. Based on a case study in a multinational bank, our results show codevelopment to be a parallel resourcing space that offsets certain organizational pressures, thereby offering valuable individual, group and organizational benefits. As an original talent development practice, codevelopment can also contribute to counterbalancing some of the downsides to talent management.